The Influence of Perceptions of The Teaching Profession on Interest in Becoming a Teacher in Economics Education Students at Panca Sakti University Bekasi - Ismeirita, Ismeirita; Ahman, Eeng; Disman, Disman (Soedirman Economics Education Journal, 2024)
The purpose of this study was to determine the effect of perceptions of the teaching profession on interest in becoming a teacher. The population of this study were Economics Education students at the Faculty of Education, Panca Sakti University Bekasi who were active in the odd semester of the 2023/2024 academic year. This sampling technique uses purposive random sampling so that a total sample of 60 people is obtained. Data collection methods include questionnaires and documentation. The data analysis method used is descriptive analysis and simple linear regression analysis. This means that the perception of the teaching profession affects the interest in teaching economics education students at Panca Sakti University Bekasi.